Tinjauan Fikih Muamalah Terhadap Penambahan Kode Unik Transfer di crowdfunding Kitabisa.Com - Nurfauziah, Anida; Muhammad, Iqbal Fadli (Department of Islamic Economics Law, 2024)
Increased cooperation and humanitarian spirit in Indonesia, supported by technological advances, has encouraged innovation in charitable activities. Kitabisa.com, a fast-growing crowdfunding platform, facilitates online donations with various payment methods, one of which is the bank transfer method. In this method, donors are required to add a unique code for automatic verification. This research aims to determine the muamalah jurisprudence review of the practice of adding a unique code at the end of payment transfers in Kitabisa. This type of research uses a qualitative descriptive method, using a literature review. Data for this research was obtained through the Kitabisa website, as well as through interviews with muamalah fiqh experts. The result of this research is that the use of unique codes on crowdfunding platforms such as Kitabisa.com is in accordance with sharia principles, namely grant contracts, because the main contract is tabarru' or social contract, so adding a unique code is considered a form of grant or voluntary contribution from the donor for the purpose of social.